2015
DOI: 10.1039/c4ta04669b
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically enhanced photoelectrochemical properties of a layer-by-layer hybrid film based on graphene oxide and a free terpyridyl-grafted ruthenium complex

Abstract: Electrostatically self-assembled multilayer films, which were formed using graphene oxide and a ruthenium complex, have been prepared. The films were characterized by UV-vis absorption spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy and cyclic voltammetry. The results indicated that the films were uniformly prepared and exhibited surface-confined metal-based redox behaviours. In addition, the films exhibited significant cathodic photocurrents that are better than the photocurrents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
(103 reference statements)
2
3
0
Order By: Relevance
“…Stable and rapidly responding photocurrents were observed and monotonically increased as the biases became more negative from +0.6 to −0.4 V versus SCE, indicating that interfacial electron transfer occurred from thin-film-modified ITO to electrolyte solution and the photocurrents generated by the films were the cathode photocurrent, which is similar to the behaviors of some Ru­(II)-complex-based electrostatic self-assembled films previously reported. , It was found that the maximum photocurrent (photocurrent densitiy) of 2.66 μA (9.6 μA/cm 2 ) was achieved at −0.4 V for the poly­( L ) 1 film. In comparison to Table , it is worth mentioning that a significant cathode photocurrent density of 2.2 μA/cm 2 at a bias potential of 0 V was observed for the poly­( L ) 1 film, which outperforms or is comparable to those previously reported for some representative molecule-based thin films under similar experimental conditions. ,,,,,,, …”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Stable and rapidly responding photocurrents were observed and monotonically increased as the biases became more negative from +0.6 to −0.4 V versus SCE, indicating that interfacial electron transfer occurred from thin-film-modified ITO to electrolyte solution and the photocurrents generated by the films were the cathode photocurrent, which is similar to the behaviors of some Ru­(II)-complex-based electrostatic self-assembled films previously reported. , It was found that the maximum photocurrent (photocurrent densitiy) of 2.66 μA (9.6 μA/cm 2 ) was achieved at −0.4 V for the poly­( L ) 1 film. In comparison to Table , it is worth mentioning that a significant cathode photocurrent density of 2.2 μA/cm 2 at a bias potential of 0 V was observed for the poly­( L ) 1 film, which outperforms or is comparable to those previously reported for some representative molecule-based thin films under similar experimental conditions. ,,,,,,, …”
Section: Resultssupporting
confidence: 70%
“…Thin-film materials of functional molecules, such as organic small molecules/polymers and metal complexes, have attracted intensive attention in photoelectronic applications, such as solar cells, light-emitting diodes, thin-film transistors, flexible displays, and electrochromic cells. The film deposition techniques, such as electropolymerization, covalent self-assembly, spin coating and drop casting, , electrostatic self-assembly, and electrospray, can usually be used for fabricating thin films of functional molecules. Among these techniques, electropolymerization presents the following competitive advantages: easy operation, cost-effective instrumentation, very rapid simultaneous realization of electrosynthesis of polymers and separation of the polymers and monomers, controllable film coverage and thickness, and varying structures and doping degrees by simply changing electropolymerization parameters, such as electropolymerization time or the number of potential sweep cycles and precursor molecules, , although spin coating and electrospray have been used in industry for film fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…These results proved that the photocurrents observed were cathodic. It is worth noting that the photocurrent (photocurrent density) observed at zero bias potential was found to be 1.6 µA (5.7 µA/cm 2 ), which compares favorably with those for most of the previously reported thin films [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. Thus, we conclude that the film we studied here may be a highly promising candidate for applications in PEC oxygen reduction or sensing.…”
Section: Pec Propertiessupporting
confidence: 86%
“…165 GO and cationic terpyridyl-Ru complexes have been shown to be electrochemically active in organic electrolytes and also photoactive, with a synergistic effect between both components. 166…”
Section: Go and Rgo In Lbl Assembliesmentioning
confidence: 99%